COMPARISON OF INDUCTION OF GENERAL ANESTHESIA WITH PROPOFOL AND SEVOFLURANE FOREASE OF I GEL INSERTION: A RANDOMISED CONTROLLED TRIAL - Akshay Chandrashekar Gundalli; MN, Vijai; Gokul B; Rathore, Vikram Singh (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objectives: The aim of this study is to compare the conditions for supraglottic airway device (I Gel) insertion following induction of anesthesia with inhalation of Sevoflurane or intravenous induction with propofol in patients undergoing short surgery (<3 h) and comparison the loss of eye reflex, Hemodynamic parameters, Jaw opening, Ease of insertion, coughing, gagging, laryngeal spasm are taken into consideration. Methods: It is randomized control trial was conducted in the Department of Anaesthesia at Command Hospital (Air Force) Bengaluru after obtaining permission from the Institutional Ethical Committee. A total of 140 patients included in the study with written consent, during the 18-month period between May 2020 and November 2021. Patients were randomized into one of the two groups as group P: Propofol and group S: Sevoflurane for induction of anesthesia. Both groups receive IV Lignocaine (2 mL of 1%) before induction of anesthesia. The grading condition for insertion between the groups were noted and compared using appropriate statistical tool using SPSS v21 operating on windows 10. Results: There was no significant difference in the mean age of patients between propofol group and sevoflurane group. Overall propofol group had the better performance compared to the sevoflurane group. There was higher incidence of repeat administration in the sevoflurane group (2.9%) compared to propofol group (1.4%), which was statistically insignificant. Conclusion: The present study found comparable results for supraglottic airway device (I Gel) following induction of anesthesia with inhalation of Sevoflurane or intravenous induction with Propofol.